FEATURES OF HORMONAL CHANGES DURING PUBERTY IN GIRLS BORN TO WOMEN WITH GESTATIONAL DIABETES - Mustafayeva, I.R.; Aliyeva, E.M.; Asadova, Sh.Sh.; Karimova, S.N.; Abbasova, F.Yu.; Safarova, S.S.; Baghirova, A.M. (World of Medicine and Biology, 2025)
With the purpose to assess the features of hormonal changes in girls born to mothers with gestational diabetes, the 25 pubertal girls born to mothers with gestational diabetes and 30 practically healthy girls. The sexual development, indicators of carbohydrate metabolism and the levels of follicle-stimulating hormone, luteinizing hormone, thyroid-stimulating hormone, prolactin, cortisol, triiodothyronine, thyroxine, dehydroepiandrosterone sulfate, 17-hydroxyprogesteron, estradiol, and testosterone were determined. In the girls from mother with gestational diabetes the hirsutism index was significantly higher (P
Keywords: gestational diabetes mellitus; puberty; hypoestrogenism; hyperprolactinemia; adrenal-ovarian hyperandrogenism